2012
DOI: 10.1161/circimaging.112.973321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Echocardiography and Biomarkers for the Extended Prediction of Cardiotoxicity in Patients Treated With Anthracyclines, Taxanes, and Trastuzumab

Abstract: Background Because cancer patients survive longer, the impact of cardiotoxicity associated with the use of cancer treatments escalates. The present study investigates whether early alterations of myocardial strain and blood biomarkers predict incident cardiotoxicity in patients with breast cancer during treatment with anthracyclines, taxanes, and trastuzumab. Methods and Results Eighty-one women with newly diagnosed human epidermal growth factor receptor 2–positive breast cancer, treated with anthracyclines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
602
7
33

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 725 publications
(706 citation statements)
references
References 26 publications
34
602
7
33
Order By: Relevance
“…Assessment of LVEF alone by either method appears insensitive to detect subclinical changes and predict subsequent cardiotoxicity. Decreases in myocardial deformation (strain) precede changes in LVEF and have been consistently predictive of cardiac dysfunction from trastuzumab 82, 83. The American Society of Echocardiography recommends global longitudinal strain measured by speckle tracking echocardiography as the modality of choice for detection of subclinical myocardial changes and risk prediction 17.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of LVEF alone by either method appears insensitive to detect subclinical changes and predict subsequent cardiotoxicity. Decreases in myocardial deformation (strain) precede changes in LVEF and have been consistently predictive of cardiac dysfunction from trastuzumab 82, 83. The American Society of Echocardiography recommends global longitudinal strain measured by speckle tracking echocardiography as the modality of choice for detection of subclinical myocardial changes and risk prediction 17.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
“…Additionally, optimal timing and frequency of measurement as well as the ideal cutoff have not yet been determined. An integrated approach using strain imaging and high‐sensitivity troponin may provide incremental value in predicting subsequent cardiac dysfunction, but needs further investigation 83. The recently published guidelines from the American Society of Clinical Oncology gives a moderate strength of recommendation for routine use of biomarkers and echocardiographic‐derived strain imaging for surveillance of cardiotoxicity, citing intermediate quality of evidence 53.…”
Section: Monitoring For Cardiac Dysfunction During Her2‐targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter study comparing echocardiographic parameters in patients with HF, global longitudinal strain (GLS) assessment, a parameter evaluating longitudinal aspect of myocardial contraction using deformation imaging, appeared to have a higher and more reliable prognostic value than LVEF for the prediction of cardiac events and cardiac deaths [20]. 2D speckle tracking strain has already been evaluated in studies for a total of more than 700 patients concomitantly to the administration of cardiotoxic anticancer agents, with encouraging results concerning its capability to diagnose subclinical LV dysfunction of subsequent clinical relevance [21][22][23][24][25][26][27]. Based on these data, serial strain measurements are suggested during anticancer treatment [11••].…”
Section: Imaging Techniques Echocardiographymentioning
confidence: 99%
“…High-sensitive troponins assays may have a greater interest for the detection of subclinical myocardial damage. Sawaya et al recently demonstrated that highsensitive Tn-I assays in combination with echocardiography strain imaging increase the accuracy of early detection and prediction of CTRCD in breast cancer patients treated with anthracyclines and trastuzumab [22,24]. The ASE/EACVI consensus document recommends serial Tn-I levels be drawn with a chemotherapy regimen potentially associated with type I or type II toxicities or in case of their sequential administration [11••].…”
Section: Circulating Biomarkersmentioning
confidence: 99%